Comparison of low-volume spray application rates using UASS: implications for vine canopy deposition, spray quality, and in-field ground losses - Eric Mozzanini; Alessandro Biglia; Fabrizio Gioelli; Alessandro Sopegno; Valeria Maritano; Chiara Messina; Paolo Gay; Marco Grella (Precision Agriculture, 2026)
Purpose This study aimed to identify stage-specific UASS operational settings for canopy-targeted one-way band spray mode in a vineyard. To this end, the trade-offs between canopy deposition, in-field ground losses, and spray quality were quantified across three growth stages. Methods Field trials were conducted at three growth stages (early, middle, late) using a canopy-targeted one-way band spray mode at fixed flight height. Five operational settings were tested, corresponding to application rates of 54.2, 72.9, 90.6, 105.8, and 142.2 L ha − 1 under the selected nozzle and pressure configurations. A dye tracer was used to quantify deposits on collectors placed in the canopy and on the ground. Spray quality was assessed with water sensitive papers to derive spray coverage and coverage density on the upper and lower leaf sides. Results Absolute canopy deposition increased with application rate; however, the vertical distribution consistently skewed towards the upper canopy, and this tendency became more pronounced at later growth stages, indicating reduced deposits within the grape band. In-field ground losses increased sharply with application rate (+ 233% from 54.2 to 142.2 L ha − 1 ). Spray coverage also increased with application rate, whereas coverage density showed a significant growth stage - application rate interaction, indicating stage-dependent optima. Conclusions Under the tested configurations, the most promising stage-specific operational settings were ISO 015 at 0.30 MPa (54.2 L ha − 1 ), ISO 03 at 0.30 MPa (105.8 L ha − 1 ), and ISO 04 at 0.25 MPa (142.2 L ha − 1 ) for the early, middle, and late stages, respectively. These outcomes should be interpreted as configuration-specific operational recommendations under the tested nozzle, pressure, and flight height conditions, rather than as universally applicable phenology-adjusted volume prescriptions. Further improvements in spray delivery to the grape band will likely require adjustments in flight height in addition to application rate selection, although this will depend on the trellis system adopted in the vineyard.

Investigating heavy metals and other elements in Procambarus clarkii and environmental matrices from three wetlands of Sicily (Italy) - Dario Savoca; Federico Marrone; Francesco Paolo Faraone; Vittoria Giudice; Salvatore Messina; Gaetano D’Oca; Vincenzo Arizza; Antonella Maccotta; Luca Vecchioni (Environmental Science and Pollution Research, 2025)
A qualitative and quantitative analysis of 18 elements was conducted on Procambarus clarkii and its environmental samples to evaluate its potential as a bioindicator species. Analysis of biological samples was carried out to both assess the safety of the use of raw materials and, together with environmental samples, to assess the contamination status of the sampled sites. Significant differences highlighted by the PERMANOVA, HCA and PCA analyses confirmed the valid use of P. clarkii as a bioindicator of the health status of the studied ecosystem. The bioaccumulation factor (BAF) and the biotic sediment accumulation factor (BSAF), except in a few cases, reported values below the bioaccumulative criterion and showed the highest BAF values for manganese, iron and barium in the exoskeleton while the highest BSAF values concerned mercury, copper and zinc in the muscle and barium in the exoskeleton. These findings indicate that, for most of the trace elements (TEs), the extent of pollution at these sites is such that it does not result in significant bioaccumulation in the muscle and exoskeleton of P. clarkii . The TE concentration levels signalled mild contamination of the sampling sites, proving a good health status of the studied aquatic ecosystem. Finally, the results obtained in P. clarkii muscle were below the threshold limits of EU Regulation 2023/915 suggesting that these edible parts are safe for human consumption.

Temperatures recorded from January 2019 to February 2023 in the high-temperature fumaroles of the active cone of La Fossa Caldera - Iole Serena Diliberto; Maria Grazia Di Figlia; Paolo Cosenza; Luigi Foresta Martin; Vincenzo Francofonte; Andrea Mastrolia; Giuseppe Messina; Giuseppe Passafiume (Bulletin of Volcanology, 2024)

High-dose anakinra in addition to standard of care including corticosteroids in patients with severe COVID-19 treated with non-invasive ventilation - Andrea Mastrangelo; Roberta Monardo; Laura Galli; Alessandro Tomelleri; Chiara Tassan Din; Diana Canetti; Emanuela Messina; Monica Guffanti; Anna Danise; Corrado Campochiaro; Giulio Cavalli; Giacomo Monti; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2023)

A 560–440 ka tephra record from the Mercure Basin, southern Italy: volcanological and tephrostratigraphic implications - BIAGIO GIACCIO; PAOLO GALLI; EDOARDO PERONACE; ILENIA ARIENZO; SEBASTIEN NOMADE; GIAN PAOLO CAVINATO; MARCO MANCINI; PAOLO MESSINA; GIANLUCA SOTTILI (Journal of Quaternary Science, 2014)
Integrated electron microprobe analyses (EMPAs) on glass and Sr–Nd isotope analyses have been performed on 17 tephras from the Middle Pleistocene Mercure lacustrine succession, southern Apennines. Two 40 Ar/ 39 Ar ages and the recognition of four relevant tephras from Colli Albani, Sabatini and possibly Roccamonfina volcanoes allowed us to ascribe the investigated succession to the late Marine Isotope Stage (MIS) 15–12 interval (560–440 ka). The Sr–Nd isotopes and major element glass compositions allowed us to attribute 10 out of the other 13 tephras to a poorly known activity of the Roccamofina volcano, whereas two layers were tentatively attributed to previously unknown Middle Pleistocene activity of Ponza Island or Campanian volcanoes, and one to Salina Island. The tephrostratigraphic correlation of the Mercure tephras with the Acerno lacustrine pollen record (Campania) also allowed us to evaluate the climatostratigraphic position of the tephras within the framework of the MIS 15–12 climatic variability. These results were obtained by combining the Sr–Nd isotope ratio with EMPA and 40 Ar/ 39 Ar geochronological data. This confirms the notable consistency of this approach for studying the Mediterranean Middle Pleistocene tephrostratigraphy, which, despite its great potential for both volcanology and Quaternary studies, has been hitherto barely explored.

Benford’s Law in Time Series Analysis of Seismic Clusters - Gianluca Sottili; Danilo M. Palladino; Biagio Giaccio; Paolo Messina (Mathematical Geosciences, 2012)

Active normal faulting along the Mt. Morrone south-western slopes (central Apennines, Italy) - Stefano Gori; Biagio Giaccio; Fabrizio Galadini; Emanuela Falcucci; Paolo Messina; Andrea Sposato; Francesco Dramis (International Journal of Earth Sciences, 2011)

Distinct changes in cortical and spinal excitability following high-frequency repetitive TMS to the human motor cortex - Angelo Quartarone; Sergio Bagnato; Vincenzo Rizzo; Francesca Morgante; Antonio Sant’Angelo; Fortunato Battaglia; Corrado Messina; Hartwig Roman Siebner; Paolo Girlanda (Experimental Brain Research, 2005)